Amisulpride for the Rescue Treatment of Postoperative Nausea or Vomiting in Patients Failing Prophylaxis: A Randomized, Placebo-controlled Phase III Trial. (February 2019) - Habib, Ashraf S.; Kranke, Peter; Bergese, Sergio D.; Chung, Frances; Ayad, Sabry; Siddiqui, Naveed; Motsch, Johann; Leiman, David G.; Melson, Timothy I.; Diemunsch, Pierre; Fox, Gabriel M.; Candiotti, Keith A.
Editor's Perspective: What We Already Know about This Topic: Although antiemetics are commonly used to prevent postoperative nausea or vomiting, the failure rate is appreciable and there is little evidence to guide best therapy for rescue treatment after failed prophylaxis What This Article Tells Us That Is New: Ten milligrams of intravenous amisulpride, a dopamine D2 /D3 -antagonist, is superior to placebo at treating established postoperative nausea or vomiting after failed prophylaxis, whereas 5 mg was not superior to placebo Background: Although antiemetics are commonly used to prevent postoperative nausea or vomiting, the failure rate is appreciable and there is currently no generally accepted standard for rescue treatment of postoperative nausea or vomiting after failed prophylaxis. This prospective, randomized, double-blind, parallel-group, placebo-controlled, multicenter study was designed to test the hypothesis that intravenous amisulpride, a dopamine D2 /D3 -antagonist, is superior to placebo at treating established postoperative nausea or vomiting after failed prophylaxis. Methods: A total of 2, 285 adult patients undergoing surgery under general inhalational anesthesia and receiving standard antiemetic prophylaxis were enrolled at 23 sites in Canada, France, Germany, and the United States. Of these, 702 patients experienced postoperative nausea or vomiting in the 24-h period after surgery and were randomized to receive a single dose of 5 or 10 mg intravenous amisulpride or matching placebo. The primary endpoint was complete response, defined as no emesis or rescue antiemetic use for 24 h after study drug administration, excluding emesis in the first 30 min. Secondary endpoints included incidence of emesis and rescue medication use, nausea burden, time to treatment failure, and length of stay in postanesthesia care unit and hospital. Results: Complete response occurred in significantly more patients receiving 10 mg amisulpride (96 of 230, 41.7%) than placebo (67 of 235, 28.5%), a 13.2% difference (95% CI, 4.6 to 21.8; odds ratio, 1.80; P = 0.006). A 5-mg dose of amisulpride did not show a significant benefit (80 of 237, 33.8%); the difference from placebo was 5.2% (95% CI, 3.1 to 13.6; odds ratio, 1.24; P = 0.109). The total number of adverse events recorded and proportion of patients with at least one adverse event were comparable between the placebo and amisulpride groups. No clinically relevant toxicities were observed. Conclusions: A single 10-mg dose of intravenous amisulpride was safe and more effective than placebo at treating established postoperative nausea or vomiting in patients failing postoperative nausea or vomiting prophylaxis. Abstract : Ten milligrams of intravenous amisulpride, a dopamine D2/D3-antagonist, is superior to placebo at treating established postoperative nausea or vomiting after failed prophylaxis, whereas 5 mg was not superior to placebo.